Neoliberalismo em jogo: o discurso neoliberal nos vídeo games entre os anos 80 à 2000 - Caron, Giuseppe Rafael (2023)
This research presents as its theme the discussion of the relations between neoliberal ideology and the video game industry. For this purpose, games that demonstrate relevance in their time and that presented innovations in the narrative, graphic capacity and gameplay were used as objects of the work. So, the selected games were: Super Mario Bros. (NINTENDO, 1985), Sonic the Hedgehog (SEGA, 1991), Doom (ID SOFTWARE, 1993) and the trilogy of the Grand Thelf Auto franchise (ROCKSTAR) for the 6th generation consoles (Playstation 2, Xbox and GameCube). Because it is an innovative source, it was necessary to use methodologies that could talk to my source, such as: “Procedural Rhetoric” from Professor Ian Bogost's and the “Wordplay” from Professor Christopher A. Paul, in which they were of importance to be able to understand the gameplay of each game. In the case of the issue of neoliberalism, the works of Christian Laval and Pierre Dardot were essential. In this sense, In this sense, In this sense, the objective of the research is to demonstrate the understanding of how the neoliberal discourse (mainly that referring to the Man-Company) has been taking root within our society and how the mechanics of electronic games reinforce this. After four years of work, it was possible to achieve the following hypotheses: Some changes in the narratives and gameplay occurred because of the neoliberal growth in the world, beyond that the trivialization of violence, mainly in digital media, a fact that is due to the unorthodox forms of how neoliberalism is imposed, by the permissions of the ManCompany to deviate morally, and finally, how work has become more painful for the worker as a result of a “liberation” from the figure of authority at work and from the clock , but who ends up replacing it with a self-guard. Therefore, as you can see, this work concludes that neoliberalism has already taken root in our society and games are an important way for us to observe this process